Fidelity Testing of Avionic Instruments in NAS 332 Super Puma Simulator Using FAA 14 CFR Part 60 - Citra Dewi Larasati; Karmilasari; Evi Endarti (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2026)
Simulation technology is increasingly vital in aviation, enhancing pilot training and reducing risks from human error. This study evaluates the fidelity of the NAS-332 Super Puma Helicopter Full Flight Simulator (FFS) Level-C, focusing on avionic instruments. The assessment aimed to determine how closely the simulator replicates the aircraft’s avionic hardware, software, and operational performance. A black-box testing approach was applied in accordance with FAA 14 CFR Part 60 Advisory Circular standards. Avionic subsystems were examined for accuracy in display layouts, response functions, and system integration. Findings show that the simulator achieves a fidelity score of 89%, confirming its reliability in replicating real-world avionics. These findings confirm the simulator’s suitability as a regulatory-compliant training tool that supports pilot proficiency and operational readiness. By highlighting avionics fidelity within the broader context of human-computer interaction and workload research, the study extends current simulation literature and contributes to improving the effectiveness of rotorcraft pilot training.